THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT PRACTICES ON THE COMPETITIVENESS OF A DAIRY COOPERATIVE: EVIDENCE FROM ANJASMORO DAIRY COOPERATIVE IN WONOSALAM, INDONESIA - Linda Marta Kusuma; Teguh Soedarto; Gyska Indah Harya (Jurnal Mahasiswa Agribisnis, 2026)
Human resource management plays an important role in improving organizational competitiveness, particularly in dairy cooperatives facing increasingly competitive market conditions. This study aims to analyze the effect of recruitment, training, compensation, and performance appraisal on the competitiveness of KUD Anjasmoro in Wonosalam District, Jombang Regency. The research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The study involved 40 respondents selected using the census method. The results indicate that recruitment, training, compensation, and performance appraisal have positive and significant effects on competitiveness. Recruitment has a path coefficient of 0.287 (T-statistic = 4.177; p = 0.000), training 0.240 (T-statistic = 2.556; p = 0.011), compensation 0.363 (T-statistic = 4.427; p = 0.000), and performance appraisal 0.361 (T-statistic = 5.174; p = 0.000). The R-Square value of 0.886 indicates that 88.6% of the variation in competitiveness is explained by these human resource management variables. Compensation and performance appraisal were identified as the most influential variables in enhancing organizational competitiveness. These findings suggest that strengthening strategic human resource management practices can improve the competitiveness of dairy cooperatives. Keywords: competitiveness, compensation, human resource management, performance appraisal, recruitment